2020
DOI: 10.1111/jsr.13169
|View full text |Cite
|
Sign up to set email alerts
|

Treating insomnia in Swiss primary care practices: A survey study based on case vignettes

Abstract: Guidelines recommend cognitive behavioural therapy for insomnia (CBT‐I) as first‐line treatment for chronic insomnia, but it is not clear how many primary care physicians (PCPs) in Switzerland prescribe this treatment. We created a survey that asked PCPs how they would treat chronic insomnia and how much they knew about CBT‐I. The survey included two case vignettes that described patients with chronic insomnia, one with and one without comorbid depression. PCPs also answered general questions about treating ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…The findings of this study indicate a discrepancy between current clinical practice and the RACGP clinical guidelines which recommend CBTi as the first line treatment for insomnia [18]. GPs rely on sleep hygiene education treatment with scarce reference to the other components of CBTi, consistent with previous research on this topic [37][38][39][40]. This is of concern given limited evidence about the effectiveness of sleep hygiene as a standalone treatment in primary care [41].…”
Section: Discussionsupporting
confidence: 65%
“…The findings of this study indicate a discrepancy between current clinical practice and the RACGP clinical guidelines which recommend CBTi as the first line treatment for insomnia [18]. GPs rely on sleep hygiene education treatment with scarce reference to the other components of CBTi, consistent with previous research on this topic [37][38][39][40]. This is of concern given limited evidence about the effectiveness of sleep hygiene as a standalone treatment in primary care [41].…”
Section: Discussionsupporting
confidence: 65%
“…The ndings of this study indicate a discrepancy between current clinical practice and the RACGP clinical guidelines which recommend CBTi as the rst line treatment for insomnia (18). GPs rely on sleep hygiene education treatment with scarce reference to the other components of CBTi, consistent with previous research on this topic (37)(38)(39). This is of concern given limited evidence about the effectiveness of sleep hygiene as a standalone treatment in primary care (40).…”
Section: Discussionsupporting
confidence: 66%
“…We conducted a structured online survey whose concept was based on a similar project aimed at PCPs and developed by Linder et al [ 17 ]. The survey was adapted to community pharmacists and separated into four different parts, comprising items on demographic data about the pharmacists and their pharmacy, questions to be answered about three clinical vignettes, general questions about insomnia and questions about the pharmacist’s broad knowledge of CBT-I.…”
Section: Methodsmentioning
confidence: 99%
“…Information about pharmacists’ knowledge of CBT-I is also lacking. Indeed, a vignette-based survey study of PCPs in Switzerland demonstrated their limited knowledge about CBT-I as well as discrepancies between the treatments they initiated and current guidelines [ 17 ]. Consequently, our hypothesis derived from these findings was, that most pharmacists in Switzerland would advise their clients to use phytopharmaceuticals alone or in combination with a non-pharmacological treatment other than CBT-I.…”
Section: Introductionmentioning
confidence: 99%